Strategic Formulation of Provincial Industry Development Using SWOT-AHP Analysis - Kungwansupaphan, Chonnatcha; Parnitvitidkun, Peevara; Suwanpusit, Ubonwan (Journal of Applied Economics and Management Strategy, 2022)
ABSTRACT The paper aims to conduct the hybrid method combined the SWOT and Analytic Hierarchy Process (AHP) analysis for strategic formulation as well as using the TOWS matrix to identify the set of priority strategies for the industry development of Surin province. The Surin province was chosen as the case study in the research to represent the majority of provinces in Thailand that need appropriate strategic industrial development to stimulate the local economy. This research employed the hybrid method, combining the SWOT analysis to determine significant strengths, weaknesses, opportunities, and threats factors, while the AHP was conducted to prioritize these factors. In the light of the SWOT-AHP results, the TOWS matrix was applied to formulate strategies. Four appropriate strategies were formulated and should be implemented for Surin industrial development, including strengthening agricultural industry competitiveness, promoting productivity in agriculture, promoting and developing essential entrepreneur skills to adapt to COVID-19 situation, and providing accessibility for short- and long-term capital sources to support entrepreneurs.